El Contador Público 4g Versus La Inteligencia Artificial (2021)
In this monograph, a study and analysis of the most important aspects of the implementation of Artificial Intelligence in the accounting field was carried out. Defining, based on the criteria of several authors, the concept of Artificial Intelligence and the most used tools today. Also, it was sought to understand the perception that students and teachers have about the possibility of being replaced in their functions, by intelligences capable of automating processes and providing solutions in decision-making. Subsequently, the advantages and disadvantages of the application of this discipline within the accounting profession were analyzed, by means of a SWOT matrix, in which the different variables that may arise as a result of the development of these technologies were compared.